2016
DOI: 10.11138/gchir/2016.37.2.061
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of minimally invasive parathyroidectomy under local anaesthesia and minimally invasive video-assisted parathyroidectomy for primary hyperparathyroidism: a cost analysis

Abstract: Primary hyperparathyroidism (PHPT) is the third most frequent disease among the endocrine disorders, with a prevalence of 1-3% in western countries. Moreover, it is the commonest cause of hypercalcemia (1-4). Nowadays, the PHPT is diagnosed increasingly due to the improvement of biochemical test; it allowed the precocious diagnosis and the identification of asymptomatic patients (5, 6). Conventional bilateral neck exploration remains the reference surgical technique, although the hyperproduction of the parathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Previously published studies [13,[36][37][38] showed several advantages favouring LA compared to GA in terms of shorter operative room occupation time, similar or shorter operative time, lower request for post-operative analgesics, and similar post-operative outcomes. Moreover, Melfa et al [38] analysed the cost of parathyroidectomy in our healthcare system. The Italian Healthcare System's reimbursement is based on the Diagnosis Related Groups (DRGs) system, adopted by the specific regional governance.…”
Section: Discussionmentioning
confidence: 98%
“…Previously published studies [13,[36][37][38] showed several advantages favouring LA compared to GA in terms of shorter operative room occupation time, similar or shorter operative time, lower request for post-operative analgesics, and similar post-operative outcomes. Moreover, Melfa et al [38] analysed the cost of parathyroidectomy in our healthcare system. The Italian Healthcare System's reimbursement is based on the Diagnosis Related Groups (DRGs) system, adopted by the specific regional governance.…”
Section: Discussionmentioning
confidence: 98%
“…It has been noted previously that MIVAP is more expensive than "open" parathyroidectomy with the patient under local anesthesia due, among other things, to the longer operative time. 2 Group A had 2 patients with bilateral disease (true negatives), whereas group B1 had none.…”
Section: Dear Editormentioning
confidence: 98%
“…The causes previously appealed were orotracheal intubation, changes in laryngeal vascular net, cricothyroid dysfunction, denervation of neck muscles, neck pain or anxiety. The role of the type of endocrine neck disease, the technique used and the extent of surgery play an unclear role in the origin of these symptoms; neither the possible advantages of minimally-invasive techniques have been clarified (5,15,(26)(27)(28)(29)(30)(31)(32)(33). Another possible risk factor for aerodigestive complaints is the intraoperative bleeding (34).…”
Section: Discussionmentioning
confidence: 99%